2009
DOI: 10.1080/01443610903118254
|View full text |Cite
|
Sign up to set email alerts
|

Symphysiofundal height growth curve and growth velocity in pregnant women in a Nigerian community

Abstract: A prospective survey of symphysiofundal height (SFH) was undertaken in 202 Nigerian pregnant women in Uromi, Edo State, Nigeria, with the objective of constructing an SFH growth chart for the pregnant population in the community. A customised gravidogram and a growth velocity curve were also constructed and compared with those derived in other regions of the world. The average SFH growth rate between 20 and 40 weeks was 0.8 cm/week. The gradient of the curve was not constant and the SFH growth rate changed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…145 SFH measured in centimeters between 24 and 38 weeks of gestation approximates the gestational age. 147 Numerous local charts are currently used worldwide, [148][149][150][151][152][153][154][155][156] with the recent addition of an international standard for SFH based on serial measurements. 145 However, the accuracy of SFH measurement in predicting SGA (EFW <10th percentile) is limited, and there are no randomized controlled trials that compare SFH measurement with serial ultrasound evaluation of fetal biometry.…”
Section: Symphysis-fundal Heightmentioning
confidence: 99%
“…145 SFH measured in centimeters between 24 and 38 weeks of gestation approximates the gestational age. 147 Numerous local charts are currently used worldwide, [148][149][150][151][152][153][154][155][156] with the recent addition of an international standard for SFH based on serial measurements. 145 However, the accuracy of SFH measurement in predicting SGA (EFW <10th percentile) is limited, and there are no randomized controlled trials that compare SFH measurement with serial ultrasound evaluation of fetal biometry.…”
Section: Symphysis-fundal Heightmentioning
confidence: 99%
“…Ebite LE et al in a prospective survey of SFH in 202 Nigerian pregnant women in Uromi, Nigeria, constructed a customized gravidogram and a growth velocity curve and compared with those derived in other regions of the world. 14 While the average SFH growth rate between 20 and 36 weeks was 0.9 cm/week, there was a marked deceleration to 0.3 cm/week from 36 to 40 weeks. The average deviation from the mean SFH was 1.96 cm.…”
Section: Discussionmentioning
confidence: 91%
“…We extracted data from studies that reported average or median SFH measurements for general obstetric populations in LMIC across weeks 20 to 40 of gestation. Nineteen unique studies (8 in Africa, 11 in Asia, 1 in South America) reported population-based reference values of SFH in LMIC [44,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65]. One study from Panama displayed graphs with 10% and 90% values, however did not display values or report on the 50% or mean and thus was not included [9].…”
Section: Population-based Reference Curves Of the Relationship Betwee...mentioning
confidence: 99%